2006
DOI: 10.1097/01.aog.0000210529.70226.0a
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Liquid-Based Cytology and Human Papillomavirus Testing in Cervical Cancer Screening

Abstract: In the U.S. Army, cervix cancer screening performed with liquid-based cytology and reflex HPV testing of atypical squamous cells of undetermined significance performed every 2 years is cost-effective, especially when indirect costs are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012).…”
Section: Results By Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012).…”
Section: Results By Outcomesmentioning
confidence: 99%
“…Chuck et al remarked that Pap smear screening every three years for all Canadian women and HPV triage for women older than 30 years with ASCUS were the most cost-effective strategies (Chuck, 2010 (Maxwell et al, 2002;Bidus et al, 2006). Berkhof et al (2010) in the Netherlands, indicated that starting screening with HPV triage with 5 years interval was the most cost effective strategies (Berkhof et al, 2010).Vijayaraghavan in South Africa reported that coscreening with HPV testing was less costly and the most effective strategy (Vijayaraghavan et al, 2009).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 3 more Smart Citations